Ma langue sur ton coeur - Guichard, Céline 1970-; Nollimerg, Maldo; Kunst, Flore; Coleman, Joe 1955-; Lee, Sarah 1989-; Lugosi, Mïrka 1958-; Van Linden, Mokeït 1963-; Musta Fior; Valsky, Romano; Tachdjian, Raphaël; Hubaut, Joël 1947-; Masséus, Marinka 1970-; et al. (Joie Panique Éditions, 2023)
Un collectif de 70 auteurs internationaux qui nous livrent textes et dessins sur le thème de l’amour
Offsetdruck
Keywords: Graphzine